Combinatorial protein engineering of proteolytically resistant mesotrypsin inhibitors as candidates for cancer therapy - Cohen, Itay (Biochem J, 2016)
Engineered protein therapeutics offer advantages, including strong target affinity, selectivity, and low toxicity, but like natural proteins can be susceptible to proteolytic degradation, thereby limiting their effectiveness. A compelling therapeutic target is mesotrypsin, a protease upregulated with tumor progression, associated with poor prognosis, and implicated in tumor growth and progression of many cancers. However, with its unique capability for cleavage and inactivation of proteinaceous inhibitors, mesotrypsin presents a formidable challenge to the development of biologic inhibitors. We used a powerful yeast display platform for directed evolution, employing a novel multi-modal library screening strategy, to engineer the human amyloid precursor protein Kunitz protease inhibitor domain (APPI) simultaneously for increased proteolytic stability, stronger binding affinity, and improved selectivity for mesotrypsin inhibition. We identified a triple mutant APPI(M17G/I18F/F34V), with a mesotrypsin inhibition constant (K(i)) of 89 pM, as the strongest mesotrypsin inhibitor yet reported; this variant displays 1459-fold improved affinity, up to 350,000-fold greater specificity, and 83-fold improved proteolytic stability vs wild-type APPI. We demonstrated that APPI(M17G/I18F/F34V) acts as a functional inhibitor in cell-based models of mesotrypsin-dependent prostate cancer cellular invasiveness. Additionally, by solving the crystal structure of the APPI(M17G/I18F/F34V)/mesotrypsin complex, we obtained new insights into the structural and mechanistic basis for improved binding and proteolytic resistance. Our study identifies a promising mesotrypsin inhibitor as a starting point for development of anticancer protein therapeutics and establishes proof-of-principle for a novel library screening approach that will be widely applicable for simultaneously evolving proteolytic stability in tandem with desired functionality for diverse protein scaffolds.